Pemaafan (Forgiveness) oleh Istri terhadap Suami yang Berselingkuh untuk Mempertahankan Keutuhan Rumah Tangga - Bella Yundari; Hari Soetjiningsih (Humanitas (Jurnal Psikologi), 2018)
Forgiveness is the attitude of individuals who have been hurt not to commit acts of revenge against perpetrators, no desire to stay away from the perpetrator, on the contrary the desire to reconcile and do good to the perpetrator, although the perpetrator has done a painful behavior. The purpose of this study is to explore more deeply about what a wife's forgiveness picture has ever been cheated by her husband. This study uses a qualitative approach involving two participants who experienced an affair by her husband to this day. The results showed that both participants have forgiven the husband who cheated, can be seen from the actions and behavior of both participants daily who still serve the needs of her husband. Participants still survive in marriage due to children, economic dependence on her husband and assume if she is divorced not necessarily participants will get a better husband than her current husband. Keywords: Forgiveness, infidelity, wife